Optimization of Friction Stir Welding Parameters for AA6061-T651 Aluminum Alloy: Defect Analysis and Process Improvement: Optimalisasi Parameter Pengelasan Gesekan Aduk untuk Paduan Aluminium AA6061-T651: Analisis Cacat dan Peningkatan Proses - Mulyadi; Rachmat Firdaus; Rahmania Sri Untari (Universitas Muhammadiyah Sidoarjo, 2023)
Friction Stir Welding (FSW) is an eco-friendly process known for high-quality joints without filler metal. This study investigated the physical properties of FSW-welded joints in AA6061-T651 aluminum alloy by varying the concave shoulder angle. Optimal process parameters were determined through Taguchi optimization using an Orthogonal Array design. Macro and micro testing revealed overlap defects, kissing bond defects, and wormholes in some samples. Systematic experimentation identified key parameters to avoid defects, including tool rotation speed, welding speed, tool tilt angle, tool indentation angle, and shoulder depth. Visual inspection and microstructural analysis played a crucial role in assessing weld quality. Optimizing welding parameters, such as rotational speed, welding speed, temperature, and tool geometry, was highlighted as crucial for defect-free joints. The study offers valuable insights for researchers and professionals in the field, promoting the advancement and application of FSW in aluminum alloy welding. Highlight: FSW: An environmentally friendly welding process with good joint quality. Defect Analysis: Identification of overlap defects, kissing bond defects, and wormholes in welded joints. Process Optimization: Determination of optimal parameters to avoid defects, including tool rotation speed, welding speed, tool tilt angle, tool indentation angle, and shoulder depth. Keyword: Friction Stir Welding, AA6061-T651 Aluminum Alloy, Welded Joint Analysis, Process Optimization, Defect Prevention